Study of Solubility of Atorvastatin using Ternary Phase Diagram for the Development of Self-Emulsifying Drug Delivery Systems (SEDDS) - Khan, Fariba; Islam, Md Saiful; Jalil, Reza-ul (Dhaka University Journal of Pharmaceutical Sciences, 2013)
Self-emulsifying drug delivery system (SEDDS) is successfully used to improve the aqueous solubility and oral bioavailability of the poorly aqueous soluble drugs. Atorvastatin calcium (ATV), a poorly aqueous soluble drug having low oral bioavailability, was the model drug for this study. The aim of this study was to find out the suitable lipid and surfactant which can be used in formulation of ATV-SEDDS and this was done using ternary phase diagram, an important tool used very essentially in optimizing SEDDS formulations. Ternary phase diagrams of lipid/surfactant/ATV mixture were constructed to generate the solubility data of ATV. Two lipids namely Capmul PG 8, Oleic acid and seven different surfactants namely Tween 20, Tween 80, Cremophor CO 40, Cremophor CO 60, Cremophor EL, Cremophor RH 40 and Cremophor RH 60 were used. For Capmul PG 8/surfactant mixture, solubilizing efficiency order was: Cremophor RH 40 > Tween 80 > Tween 20 > Cremophor CO 60 > Cremophor RH 60 > Cremophor EL > Cremophor CO 40. For Oleic acid/surfactant mixture, solubilizing efficiency order was: Cremophor RH 40 > Tween 80 > Tween 20 > Cremophor RH 60 > Cremophor CO 60 > Cremophor EL > Cremophor CO 40. Considering the solubility phase diagrams of the drug, both Oleic acid and Capmul PG 8 can be used as lipid in combination with any of the surfactants, Cremophor RH40 or Tween 80 or Tween 20 for the development of SEDDS formulations of ATV having enhanced solubility and dissolution property. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14507 Dhaka Univ. J. Pharm. Sci. 11(2): 83-91, 2012 (December)